2013
DOI: 10.1364/oe.22.001760
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a large-scale optical exceptional point structure

Abstract: We report a large-size (4-inch) optical exceptional point structure at visible frequencies by designing a multilayer structure of absorbing and non-absorbing dielectrics. The optical exceptional point was implemented as indicated by the realized unidirectional reflectionless light transport at a wafer scale. The associated abrupt phase transition is theoretically and experimentally confirmed when crossing over the exceptional point in wavelengths. The large scale demonstration of phase transition around except… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
86
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 156 publications
(89 citation statements)
references
References 21 publications
3
86
0
Order By: Relevance
“…Unlike the Hermitian case, the levels approach each other in the form of a cusp rather than a smooth approach because of the plain square-root behavior of the singularity ( Figure 9C) [1,4]. Similar to other classical optical systems that have EPs [102], we observe that a generalized power decreasing phase and a generalized power increasing phase are divided by the EP at f = 193.4 THz ( Figure 9E). In addition, an abrupt phase change in the differential generalized power spectrum is observed at the EP as well ( Figure 9E).…”
Section: ) Ssupporting
confidence: 56%
See 2 more Smart Citations
“…Unlike the Hermitian case, the levels approach each other in the form of a cusp rather than a smooth approach because of the plain square-root behavior of the singularity ( Figure 9C) [1,4]. Similar to other classical optical systems that have EPs [102], we observe that a generalized power decreasing phase and a generalized power increasing phase are divided by the EP at f = 193.4 THz ( Figure 9E). In addition, an abrupt phase change in the differential generalized power spectrum is observed at the EP as well ( Figure 9E).…”
Section: ) Ssupporting
confidence: 56%
“…Therefore, the question arises as to whether it is possible to achieve asymmetric reflection in a non-PT-symmetric system by tuning only the real or only the imaginary part of the refractive index of the material. Feng et al recently demonstrated unidirectional reflectionless light transport at EPs in a conventional large-sized nonperiodic multilayer structure, which was fabricated by alternating thin film depositions of lossy amorphous silicon and lossless silica layers on a cleaned glass wafer using plasma-enhanced chemical vapor deposition (43 nm silica/9 nm silicon/26 nm silica/23 nm silicon; Figure 8A) [102]. The refractive index of silica at the wavelength of interest is 1.46, and the complex refractive index of amorphous silicon is 4.86 + iγ, so that the proposed structure is clearly non-PT-symmetric.…”
Section: ) Smentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the acoustic PT -symmetric setup cannot be regarded as invisible in any case, even though the system is reflectionless for the waves propagating from the left. We also notice that a well-designed lossy medium can have unidirectional reflection when operating at the exceptional points (EP) of this non-Hermitian system [31]. However, unidirectional transparency can only be realized in the PT system with gain included, since the transmission must be unitary and the unidirectionally scattered light is produced by the gain part.…”
Section: Scattering Propertiesmentioning
confidence: 97%
“…Although the concept of PTsymmetric quantum mechanics, as a fundamental theory, is still under a heated debate [27], it has been explored in optics and electronics by means of interleaving balanced gain-and-loss regions. Several interesting physical features have been explored, such as power oscillations [28], unidirectional invisibility [29][30][31][32], the reconfigurable Talbot effect [33], and coherent perfect laser absorbers [34,35]. Moreover, in the nonlinear domain, PT symmetry has been used to realize potential optical isolators and circulators [36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%